Development and characterization of two porcine monocyte-derived macrophage cell lines - Chitko-McKown, Carol G.; Chapes, Stephen K.; Miller, Laura C.; Riggs, Penny K.; Ortega-Villicana, Teresa; Green, Benedict T.; McKown, Richard D. (My University, 2013)
Cell lines CΔ2+ and CΔ2- were developed from monocytes obtained from a 10-month-old, crossbred, female pig. These cells morphologically resembled macrophages, stained positively for α-naphthyl esterase and negatively for peroxidase. The cell lines were bactericidal and highly phagocytic. Both cell lines expressed the porcine cell-surface molecules MHCI, CD11b, CD14, CD16, CD172, and small amounts of CD2; however, only minimal amounts of CD163 were measured. The lines were negative for the mouse marker H2K[superscript k], bovine CD2 control, and secondary antibody control. Additionally, cells tested negative for Bovine Viral Diarrhea Virus and Porcine Circovirus Type 2. Therefore, these cells resembled porcine macrophages based on morphology, cell-surface marker phenotype, and function and will be useful tools for studying porcine macrophage biology.
Keywords: Monocyte; Macrophage; Cytokine; Phagocytosis; Morphology; Cell surface molecule